INTEGRATION WITH THE SOFTWARE INTERFACE OF THE COM SERVER FOR AUTHORIZED USER - Denis Ratov (Applied Computer Science)
The article is devoted to the development of a software controller for automation of access to tools and object model of the multifunctional graphic editor Adobe Photoshop. The work of the graphic editor is initiated in the form of a COM object, which contains methods available to the software controller through the COM interface, which allows the software to use the functionality of the editor. To restrict unauthorized access, a software authorization control protocol is proposed, which is based on the use of binding to the computer hardware and encryption by a 128-bit MD5 public key hashing algorithm.